Isolation of Acinetobacter in patients admitted to Intensive Care Units - Midiela López López; Juan Rafael Zerquera Rodriguez; Midiala Iglesias López; Yanet Rodríguez Zulueta (Medisur)
Foundation: in the last years bacterias of the Acinetobacter gender have adquired great epidemiological relevance in gardual ascending way, due to its emergence as an opportunistic pathogen. Objective: to characterize microbiological isolations of Acinetobacter in patients admitted to the Intensive Care Units at the Provincial Hospital Dr Gustavo Aldereguia Lima. Methods: descriptive study which included the 231 Acinetobacter isolations of samples from Intensive Care Units in the period September 1st 2015 to September 30th 2016 in the Cienfuegos Provincial Hospital. The following variables were analyzed: Wards from which the isolation was coming from, type of sample, antimicrobial susceptibility in vitro and specie. Results: the highest number of Acinetobacter isolations was obtained at the Polyvalent Intensive Care Unit (62,3%). Acinetobacter baumannii was the most isolated specie with a 92,2%. Respiratory exudate were the samples with more isolations (53,3%). More than 80% of the isolations were resistant to most β-lactam antibiotics and it was found a high percentage of multi-drug and pan-drug resistant strains (41,6% and 48,1% respectively). Conclusion: the Acinetobacter gender is linked to infections connected to Sanitary Services mainly the Acinetobacter baumannii and in the Intensive Care Units.